Conflicted Hegemony: Women and Media in Lithuania and European Union - Tereškinas, Artūras (Sociologija. Mintis ir veiksmas, 2004)
Recent research has demonstrated that there has been little improvement in quality of media coverage of women in Lithuania. Women’s images are usually sexualized, stereotyped or simply negative. In the media portrayals, women are often confined to the private sphere of home. The article focuses on media representations of women in the context of women-and-media policies in EU and Lithuania. Analyzing the EU, UN and Lithuanian communication policy documents and describing briefly the key media and gender issues in EU and Lithuania, it demonstrates the lack of gender-equal media policy and the sluggishness with which the existing media policy with regard to gender issues is enforced in Lithuania. Addressing the pluralism of women’s roles and images in the media, and fair and sufficient media coverage of women, the article also discusses feminist and post-feminist media studies that could offer more complex and sophisticated media research strategies. The article also proposes some recommendations that could change, to some degree, the existing media and gender situation for the better. The author suggests that policy recommendations need a strong network of public, official and private institutions in order to be implemented successfully. Placing considerable importance on eliminating stereotypes of women and on promoting diverse and nonstereotyped images of women in the media, the article uses the term “conflicted hegemony”. “Conflicted hegemony” implies that the media provide a site for conflicts and debates over different interpretations of the dominant culture, and that ideological counter-tendencies always appear in the dominant ideological forms. Policy recommendations, media research techniques and alternative media interpretations by their consumers can serve as resistance strategies to this hegemony.